2007
DOI: 10.3324/haematol.11279
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated adenovirus infections after allogeneic hematopoietic stem cell transplantation: incidence, risk factors and outcome

Abstract: We analyzed the factors and outcome of patients with disseminated adenovirus infection (dAdV) after allogeneic hematopoeitic stem cell transplantation (HSCT). Thirty patients with dAdV were identified among 620 allogeneic HSCT recipients. Primary diseases were leukemia (n=17), Fanconi anemia (n=12) or others (n=1). Source of stem cells was unrelated in 28 and related in 2 patients. The graft consisted of peripheral blood (n=3), bone marrow (n=12) and unrelated cord-blood (UCB, n=15). Risk factors for dAdV in u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
104
4
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(118 citation statements)
references
References 22 publications
7
104
4
3
Order By: Relevance
“…1,4,7,30 Although AdV disease usually occurs between 2 and 3 months after transplant, screening studies in the pediatric setting showed that the median time point of the first AdV detection in stool specimens, urine or PB varies between days þ 12 and þ 44, which might open a window for early initiation of therapy. 1,4,5 Lethal AdV disease seems to occur particularly during the first 100 days after transplantation, regardless of AdV-directed antiviral therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,4,7,30 Although AdV disease usually occurs between 2 and 3 months after transplant, screening studies in the pediatric setting showed that the median time point of the first AdV detection in stool specimens, urine or PB varies between days þ 12 and þ 44, which might open a window for early initiation of therapy. 1,4,5 Lethal AdV disease seems to occur particularly during the first 100 days after transplantation, regardless of AdV-directed antiviral therapy.…”
Section: Discussionmentioning
confidence: 99%
“…29,[31][32][33] However, the observations made at our and other institutions indicate that initiation of antiviral treatment at the time of first detection of viremia may not prevent progression to severe AdV disease in many instances, and that earlier initiation of preemptive treatment could therefore be beneficial. 1,7,11,21,30,[33][34][35][36] Adenoviruses are known to persist in epithelial cells and lymphoid tissue, and AdV infections occurring during the posttransplant period appear to result from virus reactivation in most instances. Our observations revealed that virtually all patients who experienced systemic AdV infection had the virus detectable in serial stool specimens, with or without clinical symptoms of enteritis, before the onset of viremia.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is strengthened by the fact that CD46 is also a receptor for adenovirus, which is more frequent after CBT compared with other source of HSC. 35 Another hypothesis to explore is the particular pattern of immune reconstitution after CBT. We have compared immune reconstitution between CB and PBSCs transplants showing that, at least during the first 6 months, B lymphocytes and NK cells count were higher among CBT patients, whereas the CD8 count was lower.…”
Section: Discussionmentioning
confidence: 99%
“…Specimens positive for KIPyV or WUPyV were tested for adenoviruses; human bocavirus; human rhinoviruses; human metapneumovirus; human coronaviruses OC43, 229E, NL63, HKU1; and human PyVs BK and JC by using PCR methods (6)(7)(8)(9)(10)(11). Total nucleic acid was extracted from 200 μL of NA, BAL, or stool specimens by using the EasyMag System (bioMérieux, Marcy l'Etoile, France).…”
Section: The Studymentioning
confidence: 99%